(3QSGdI aj efLRGJ GdeQjVs - (3Gdbej, GdejQRG Gdbej, Gdbej, CHh GdbGSe Hf eMeO MSjf Gdbej, J (B1231(3g` (B1816(3es ((3cQHdGAs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg hMOg, CfLR hYOg, hfUQ YHOg (B... (3agPg QSGdI aj efLRGJ GdeQjV (B.. (3hYLGdI aj JhVjM Mce eJHQYGJ GdeTGQa HGdehJ (B... (3afbhd(B: (3GJab GdCUMGH Hd GdYdeGA XGgkQG ceG GOYGg ZjQ hGMO Ydi Cf GdhUjI EfeG jLhR aj GdKdKs
(3BNQgG (B:s
(3BNQgG(B: (3hPgH GdTjN aj W hGHf HGHhjg hGHf GdLfjO hGdeMbb hGdYdGeI aj CcKQ aJGhjgeG eY XghQ GdJQOO ef GdYdGeI aj cJGH GdMLQ ef GdEQTGO hcGdeMbb aj cJGH GdhUd ef GdTQGFY hGdTHgGJ hZjQge ef GdeJCNQjf Edi CfgeG ef GdKdK hGdPj jXgQ ef Gdabjg ehGabJg ddbhd GdChds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B5: 183s
(3GdPQjYI, L (B23: 13s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis